UN Law on International Sales - Schlechtriem, Peter. author. aut Link
LIV, 352 p.
Keywords: This book is dedicated to Professor Schlechtriem and his tremendous life time work on the United Nations Convention on the International Sale of Goods (CISG) and all past, present, and future participants of the Willem C Vis Moot for whom hopefully the book will be of some use. To have been asked to adopt Professor Peter Schlechtriem’s German text book Internationales UN-Kaufrecht (4 ed, Mohr Siebeck, Tübingen, 2007) for the English speaking student, academic, and practitioner and to work with Professor Schlechtriem on this edition has been a great honour. Unfortunately this book has been longer in the making than originally planned and more unfortunately still was not finished in time for Professor Schlechtriem to see its publishing. The aims of this book are more modest than other compendious treatments of the CISG. The main aim above all others has been to facilitate discussion on the use and application of the provisions of the CISG. As the CISG itself was the outcome of nearly a decade of debate between nations polarised in ideology, the importance of continuing discussion cannot be understated. This is especially true in regard to common law countries like Canada, Australia, and New Zealand which have all ratified the CISG many years ago but where its use and jurisprudence are rather underdeveloped.